2014
DOI: 10.1111/all.12420
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of IgE‐targeted vs empiric six‐food elimination diets for adult eosinophilic oesophagitis

Abstract: Histological remission was accomplished in 73% of patients undergoing sIgE-ED, which was nonsignificantly superior to SFED. sIgE effectively identified cow's milk as a food trigger in IgE-sensitized patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 33 publications
4
53
1
2
Order By: Relevance
“…SFED diets have also proven to be more effective than allergy testing directed therapy in a small retrospective cohort of 31 patients at UNC-Chapel Hill. SFED showed greater symptom improvement rate (78% vs. 68%) histological response rate (75% vs. 50%) and histological remission rate (56% vs. 32%) [87]. This data was also supported in a meta-analysis, by Arias, in which SFED (72.1%) was significantly better than Targeted Diet (45.5%).…”
Section: Empiric Elimination Dietsupporting
confidence: 56%
See 1 more Smart Citation
“…SFED diets have also proven to be more effective than allergy testing directed therapy in a small retrospective cohort of 31 patients at UNC-Chapel Hill. SFED showed greater symptom improvement rate (78% vs. 68%) histological response rate (75% vs. 50%) and histological remission rate (56% vs. 32%) [87]. This data was also supported in a meta-analysis, by Arias, in which SFED (72.1%) was significantly better than Targeted Diet (45.5%).…”
Section: Empiric Elimination Dietsupporting
confidence: 56%
“…Studies have shown that loss of tolerance of foods such as milk or nuts can occur when food is removed [87]. Therefore, patients with significant food specific IgE serum levels or positive skin prick testing should, according to the guidelines from Journal of Allergy and Clinical Immunology in 2011, be supplied with an injectable epinephrine to guard against anaphylaxis [17].…”
Section: Empiric Elimination Dietmentioning
confidence: 99%
“…That said, in recent years, EoE remission rates of over 70% have been reported for adults treated with an empiric 6-food elimination diet [24] and diets based on allergy tests [25]. The allergic mechanism of EoE involves both IgE and non-IgE processes [26], possibly explaining why treatment with diets based on immediate hypersensitivity test results fails in approximately 30% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Among studies that examined the effectiveness of monoclonal antibody treatment in EoE subjects, 80% defined histological remission as peak esophageal eosinophil counts within the range of 0 to ≤5 24, 25, 26, 27, 28. Approximately 26% (N = 15) of the eligible studies examined remission among EoE patients who received only the diet elimination treatment formula (SFED, FFGED, ELED) compared to other forms of treatment, with the most common definitions falling within 0 to ≤5 eosinophils/hpf 29, 30, 31, 32, 33, 34 or 11 to ≤15 eosinophils/hpf 35, 36, 37, 38, 39, 40. Interestingly, even among the SFED studies (N = 9), five studies defined remission within the range of 0 to ≤5 eosinophils/hpf, 29, 30, 31, 32, 34 and two studies considered histological remission as <15 eosinophils/hpf 38, 41…”
Section: Resultsmentioning
confidence: 99%
“…Of the 22 studies selected from European centers, 12 studies (55%) considered values within the range 11 to ≤15 eosinophils/hpf 17, 36, 37, 38, 39, 46, 47, 53, 54, 55, 56, 57, 58 as histological remission, and 4 studies (23%) defined histological remission as less than 5 or ≤ 5 eosinophils/hpf 30, 33, 42, 45. Strikingly, all studies conducted in Switzerland used a more stringent and consistent end‐point of <5 eosinophils /hpf to identify cases of histological remission 28, 59, 60…”
Section: Resultsmentioning
confidence: 99%